Denialism as Detrimental Epistemic Friction: Contexts, Agents, and the Politics of Disruption - ARBIZU AGUIRRE, Laida (Studia Universitatis Babeș-Bolyai Philosophia, 2025)
This article conceptualizes denialism as a systemic phenomenon rooted in both contextual and agentive dynamics, framing it as a form of detrimental epistemic friction. Departing from reductive approaches that treat denialism primarily as misinformation or individual cognitive bias, the analysis foregrounds the structural mechanisms through which denialism is produced, sustained, and normalized. By situating denialism within weaponized epistemic environments, the analysis shows how it reinforces power asymmetries and undermines the epistemic conditions required for inclusive and cooperative reasoning. The article provides both a diagnostic framework for identifying structural epistemic vulnerabilities and a basis for restoring democratic epistemic practices in contested knowledge landscapes.